2010
DOI: 10.5539/jas.v2n1p72
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cowpea Mottle Virus and Cucumber Mosaic Virus on the Growth and Yield of Six Lines of Soybean (Glycine Max L.)

Abstract: Cowpea mottle virus is of localised importance on cowpea in Nigeria infecting several leguminous species and Cucumber mosaic virus is of worldwide distribution infecting several horticultural crops.A study was carried out in the screen house of the crop production pavilion,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 2 publications
2
7
0
1
Order By: Relevance
“…This corroborates the findings of Alegbejo [19] who reported that the proximity of pepper plants to certain important weed hosts also has contributed greatly to the spread of viral diseases of pepper. These weeds include Solanum nigrum, S. gracil, Physalis angulata, Vigna rosea, Vigna sinensis, Commelina nudiflora, Petunia hybrida, Physalis floridana, P. micrantha and Solanum incanum .…”
Section: Resultssupporting
confidence: 92%
“…This corroborates the findings of Alegbejo [19] who reported that the proximity of pepper plants to certain important weed hosts also has contributed greatly to the spread of viral diseases of pepper. These weeds include Solanum nigrum, S. gracil, Physalis angulata, Vigna rosea, Vigna sinensis, Commelina nudiflora, Petunia hybrida, Physalis floridana, P. micrantha and Solanum incanum .…”
Section: Resultssupporting
confidence: 92%
“…Infection due to CABMV has resulted in yield losses that ranged from 13 to 87 % and sometimes total crop loss could be encountered depending on the level of susceptibility of the cultivars (Alegbejo, 2015). Besides sole infection, CABMV can co-exist with other viruses like Cowpea mottle virus (CPMoV) or CMV (Arogundade et al, 2010), causing a mixed or combined infections with more damaging effect on farmers' field. Although a lot of studies have been conducted to determine the pathogenicity of CABMV disease on cowpea there is scanty information on the effect of the virus on groundnut in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 75 to 80 % of world's groundnut is grown by resource poor smallholder farmers in developing countries who routinely obtain yields of 500 -800 kg ha -1 as opposed to the potential yields of >2.5 t ha -1 (Idem and Showemimo, 2005). Low yields are mainly due to numerous diseases caused by fungi, viruses, bacteria and nematodes (Arogundade et al, 2010;Aliyu et al, 2011;Osei et al, 2013). Diseases in groundnut caused by Blackeye cowpea mosaic virus (BICMV), Cucumber mosaic virus (CMV), Groundnut bud necrosis virus (GBNV), Groundnut rosette virus (GRV), Indian peanut clump virus (IPCV), Peanut clump virus (PCV), Peanut mottle virus (PeMoV), Peanut stripe virus (PStV), Tobacco streak virus (TSV) and Tomato spotted wilt virus (TSWV) are the most economically important and are responsible for serious yield losses globally or regionally (Taiwo, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…They are also known to naturally infect several other crops and inflict significant losses in them. Blackeye cowpea mosaic virus is a major virus disease of legume (Arogundade et al, 2010). It is flexuous, rod-shaped particles 750 mm long which induces characteristic pinwheel inclusions in infected cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation